Durability of INI-containing regimens after switching from PI-containing regimens: a single-centre cohort of drug-experienced HIV-infected subjects - Giacomelli A; Ranzani A; Oreni L; Gervasi E; Lupo A; Ridolfo AL; Galli M; Rusconi S (Dove Medical Press, 2019)
Andrea Giacomelli, Alice Ranzani, Letizia Oreni, Elena Gervasi, Angelica Lupo, Anna Lisa Ridolfo, Massimo Galli, Stefano RusconiIII Infectious Disease Unit, Department of Biomedical and Clinical Sciences "L. Sacco", University of Milan, Milan, ItalyPurpose: Integrase inhibitor (INI)-containing regimens are increasingly replacing protease inhibitor(PI)-containing regimens in clinical practice. The aim of this study was to evaluate the determinants of the durability of INI-containing regimens after the switch.Patients and methods: We retrospectively analysed all of the people with HIV infection attending the University of Milan’s Infectious Diseases Unit at Luigi Sacco Hospital who were switched from a PI- to an INI-containing regimen between April 2008 and March 2017. The probability of remaining on an INI-containing regimen was estimated using Kaplan-Meier curves, and the baseline clinical predictors of INI-containing regimen durability were assessed using a multivariable Cox proportional hazard regression model.Results: Three hundred and twelve patients were included in the analysis. The median time of observation was 21 months (interquartile range 10–36 months). The main reasons for switching from a PI-containing regimen to an INI-containing regimen were toxicities (31.4%) and simplification (31.1%). Univariate analysis revealed no difference in the probability of INI discontinuation between the patients treated with raltegravir, dolutegravir or elvitegravir (p=0.060), but the multivariable Cox regression model showed that the patients treated with dolutegravir were at less risk of discontinuation than those treated with raltegravir (adjusted hazard ratio 0.49, 95% confidence interval 0.26–0.95; p=0.034).Conclusion: Switching from a PI- to an INI-containing regimen may be an option for patients under virological control. The patients switched to dolutegravir were less likely to discontinue the INI than those switched to raltegravir. Our findings support this therapeutic strategy and highlight the durability and efficacy of dolutegravir containing-regimens after switching from a PI-containing regimen.Keywords: HIV, protease inhibitors, integrase inhibitors, dolutegravir, lipids, Framingham